Wetlands of Bangladesh - Khan, Md. Salar; Bangladesh Centre for Advanced Studies; Nature Conservation Movement (Bangladesh) (Dhaka : Bangladesh Centre for Advanced Studies in association with Nature Conservation Movement, 1994)
Contributed articles.
Includes bibliographical references (p. 77-88) and index.
Keywords: Wetlands -- Bangladesh; Wetland conservation -- Bangladesh